2009
DOI: 10.1002/mc.20550
|View full text |Cite
|
Sign up to set email alerts
|

Specific IKKβ inhibitor IV blocks streptonigrin‐induced NF‐κB activity and potentiates its cytotoxic effect on cancer cells

Abstract: Many anticancer agents activate NF-kappaB, which plays an important role in the survival of cancer cells. Inhibition of NF-kappaB activity may therefore potentiate the efficacy of anticancer agents. We found that a previously used anticancer agent Streptonigrin (SN) was also a potent NF-kappaB inducer. Using a specific IKKbeta inhibitor IV (Podolin et al., J Pharmacol Exp Ther 2005; 312: 373-381), we revealed that the activation of NF-kappaB was mediated through DNA damage-induced activation of IKK complex. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To further demonstrate the role of NF-B in Tax-mediated induction of SOCS1, we used a cell permeable small molecule inhibitor with selectivity for IKK␤ (IKK2 inhibitor IV) (11). We first validated the inhibitor by demonstrating a potent block in TNF-induced activation of an NF-B luciferase reporter gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further demonstrate the role of NF-B in Tax-mediated induction of SOCS1, we used a cell permeable small molecule inhibitor with selectivity for IKK␤ (IKK2 inhibitor IV) (11). We first validated the inhibitor by demonstrating a potent block in TNF-induced activation of an NF-B luciferase reporter gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Streptonigrin is converted by NAD(P)H:quinine oxidoreductase (NQO1) to the more active hydroquinone form. Therefore, tumors containing high levels of this enzyme might be sensitive to streptonigrin at concentrations that do not generate severe side effects [39]. It was also shown that streptonigrin at 0.05 µM markedly decreased clonogenic survival of pancreatic cancer cells expressing NQO1 at elevated levels but not of colorectal cancer cells with lower levels of this enzyme [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the control IKK-β inhibitor (IKK-β inhibitor IV), 44 compound 8 inhibited TNF-α-induced luciferase activity dose-dependently. The inhibitory effect (IC 50 : 5.85 ± 0.97 μM, Fig.…”
mentioning
confidence: 91%